A modified adaptive control method for synchronization of some fractional chaotic systems with unknown parameters - Agrawal S.K.; Das S. (My University, 2025)
A modified adaptive control method is developed in this article and the parameters identification method is then applied in fractional order systems with unknown parameters. The new modified control method based on Lyapunov stability theory is successfully applied to investigate the synchronization of pair of fractional order systems amongst Genesio-Tesi, Qi and Chen systems. By means of the Adams-Bosford-Moulton method, the numerical results show that the modified method is easy to implement and reliable for synchronizing the two different fractional order chaotic systems. © 2013 Springer Science+Business Media Dordrecht.